Copper-Catalyzed Cross-Coupling of Aryl- and Heteroaryltriethoxysilanes with Aryl and Heteroaryl Iodides and Bromides - Gurung, Santosh K.; Thapa, Surendra; Shrestha, Bijay; Giri, Ramesh (Synthesis, 2014)
Copper(I)-catalyzed coupling of aryl- and heteroaryltriethoxysilanes with aryl and heteroaryl iodides is described. The transformation also proceeds with activated aryl bromides, but in this case it requires a stoichiometric amount of the catalyst for best product yields. The current reaction requires a P,N-based bidentate ligand for aryl–aryl coupling while it proceeds without external ligands for aryl–heteroaryl coupling to afford good product yields. The reaction protocol can also be applied to achieve biarylation of diiodoarenes in reasonable yields.
Keywords: aryltriethoxysilane; biarylation; catalytic cycle; cross-coupling; P,N-ligand